A Ureteroileal Anastomosis Technique: Simple Modification To The Bricker Technique, A Retrospective Study - Serkan Özcan; Yüksel Yılmaz; Osman Köse; Yigit Akın; Sacit Nuri Görgel; Enis Mert Yorulmaz (Van Tıp Dergisi, 2020)
INTRODUCTION: We present a modification to the Bricker technique involving 124 anastomoses in a 62-patient series, and the outcomes of the procedures that have been carried out successfully to date in our clinic. METHODS: The study sample included patients who applied to our clinic for whom a radical cystectomy procedure was decided between 2012 and 2018. Among these patients, a retrospective evaluation was made of 62 patients on whom a diversion was performed using a modified Bricker technique during a radical cystectomy. RESULTS: The mean duration of follow-up was 15.9+-14 months, with a maximum of 59 months. There were 2 (3.2%) women among 62 patients. The preoperative stage was T3a in 5%, T2 in 56% and T1 high-grade in 39%. Among the 62 Bricker operations (124 anastomoses) carried out using the modified technique at our clinic, only one patient, who was stage T3b and who was being treated with postoperative adjuvant chemotherapy, developed left ureterohydronephrosis (0.8%). No stricture was observed in the other 123 anastomoses; and there were no late complications such as metabolic disturbance, stomal stenosis, pyelonephritis or lithiasis during the follow-up of the 62 patients who underwent a Bricker diversion. DISCUSSION AND CONCLUSION: We believe that the lack of anastomotic leakage in none of the operated patients and the occurrence of stricture in only one of 124 anastomoses in 62 patients is evidence of the success of the technique.